STRATEGI KOMUNIKASI KOMUNITAS LKBC DALAM PEMENUHAN KEBUTUHAN INFORMASI ANGGOTA PADA PENCARIAN LOWONGAN PEKERJAAN DI KOTA BATAM - Br Simanjuntak, Pitriani; Rorong, Michael Jibrael (SCIENTIA JOURNAL, 2022)
Community is a social group whose members are two or more people who are interconnected witheach other. The community tries to provide information about knowledge, professions and how tosolve problems. The Batam City job vacancy community (LKBC) is a social group that workstogether to find information on job vacancies in Batam City. The number of members of the BatamCity job vacancy community (LKBC) is 7 people. The Batam City job vacancy community (LKBC)once started to gather at the Marina around Batu Aji. The purpose of the study was to identifycommunication patterns applied by the Batam City job vacancy community (LKBC) regardingmeeting the information needs of seeking vacancies for members of job seekers, recognizinginformation dissemination of Batam City job vacancies community (LKBC) to members of the jobseeker group and recognizing how to utilize information media. related to the dissemination ofinformation by the Batam City job vacancies community (LKBC). Research data collectiontechniques through in-depth interviews, observation, documentation and literature study referencesources. The research data analysis method is through the Miles and Huberman analysis model.The results of research on the Batam City job vacancy community (LKBC) carry out interpersonalcommunication patterns, dissemination via telegram media and utilizing telegram media asinformation media. Conclusion through community information search can meet the informationneeds of members in the search for job vacancies in Batam